Influence of the RAFT Agent on the Reaction Direction of the Copolymerization of Polypropylene Glycol Maleate with Acrylic Acid - Kazhmuratova, A.T.; Zhunissova, M.S.; Plocek, J.; Fomin, V.N.; Sarsenbekova, A.Zh.; Khamitova, T.O. (Karagandy University of the name of acad. E.A. Buketov, 2022)
This work demonstrates the capability of synthesizing new polymers based on unsaturated polyester and acrylic acid in the presence of a chain-transfer agent in a dioxane solution. The initial unsaturated polyester resin was derived from the polycondensation reaction of alcohol and maleic anhydride. The molecular weight of the polypropylene glycol maleate was determined by gel permeation chromatography. The dependence of the structure, network density and product yield on the concentration of the RAFT agent was proven. It was found that the greater the amount of chain-transfer agent in the monomer mixture, the lower the yield of the crosslinked polymer and the greater the yield of the branched copolymer. The composition of the studied co-polymers was determined by FTIR spectroscopy in conjunction with the chemometric method of partial list squares in the R environment. The synthesized objects were characterized by infrared spectroscopy methods and were approximated by Gaussian contours. The study results show that the RAFT agent concentration, as well as the initial ratio of monomers in the copolymer affects the products yield. The surface topography of the studied copolymers was recorded by scanning electron microscopy. The molecular chain structure of the branched copolymers was confirmed by NMR spectroscopy.
RAFT-агентінің полипропиленгликольмалеинатының акрил қышқылымен сополимерлену реакциясының бағытына әсері
Влияние RAFT-агента на направление реакции сополимеризации полипропиленгликольмалеината с акриловой кислотой
Keywords: unsaturated polyester; polypropylene glycol maleate; acrylic acid; RAFT-polymerization